2020
DOI: 10.2478/frp-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Site index research: a literature review

Abstract: The purpose of this paper was to review literature covering the topic of site index with particular emphasis on Scots pine, the most important forest-forming species in Poland. We discuss the history of the site index, research on various tree species, statistical modelling methods, the spatial application of site index and age impact assessment. The history of research on the site index of forest species is long and dates back to the 18th century. Many researchers thought that determining the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…304-305)). Site index is used across the world [16][17][18]. Conceptually, for a particular species, site index is a collective influence of soil factors and climatic conditions, and when excluding extremes, site index is thought to be independent of stand density ( [13,14] and [15] (p. 303)).…”
Section: Site Quality Estimationmentioning
confidence: 99%
“…304-305)). Site index is used across the world [16][17][18]. Conceptually, for a particular species, site index is a collective influence of soil factors and climatic conditions, and when excluding extremes, site index is thought to be independent of stand density ( [13,14] and [15] (p. 303)).…”
Section: Site Quality Estimationmentioning
confidence: 99%
“…Ważyński (1967) found that the determination of the SI of pine stands up to 10 years old using height is inaccurate, because the height of young stands is not as strongly dependent on the environmental conditions as in later periods. Likewise, it is impossible to determine the site productivity by phytocentric methods for non-forest areas (Vanclay, 1994;Skovsgaard & Vanclay, 2008a;Weiskittel et al, 2011;Kędziora et al, 2020;Tymińska-Czabańska et al, 2021). Furthermore, a limitation of phytocentric methods is that they limit the possibility of identification of individual biological determinants of growth, precluding continuous mapping of SI across the landscape, or direct predictions based on environmental variables.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a limitation of phytocentric methods is that they limit the possibility of identification of individual biological determinants of growth, precluding continuous mapping of SI across the landscape, or direct predictions based on environmental variables. To solve these problems, for direct site productivity modelling the geocentric method is used, in which SI is predicted from multiple environmental factors (Skovsgaard & Vanclay, 2008b;Weiskittel et al, 2011;West, 2014West, , 2015Kędziora et al, 2020).…”
Section: Introductionmentioning
confidence: 99%